2006
DOI: 10.1097/00042737-200605000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of triple and quadruple Helicobacter pylori eradication therapies in Iranian children: a randomized clinical trial

Abstract: With regard to recent recommendations, we also suggest PPI, amoxicillin and clarithromycin triple therapy as a first-line eradication treatment, and quadruple therapies as a second-line option, in Iranian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…A similar study done by Kato et al in Japanese children showed eradication rates of 87.5% for proton pump inhibitors (PPI), amoxicillin, and metronidazole, and 77.4% for PPI, amoxicillin, and clarithromycin [13]. However in 2004 Bahremand et al preformed a study in Tehran, Iran, that showed eradication rates of 92% for omeprazole, clarithromycin, and amoxicillin and 84% for omeprazole, amoxicillin, metronidazole, and bismuth subcitrate, thus suggesting PPI, amoxicillin, and clarithromycin triple therapy as first-line eradication treatment in Iranian children [14]. Many studies preformed in adult populations have showed regimes containing amoxicillin-clavulanic acid to be more effective than those with amoxicillin in treatment of H. pylori infection [9,10,15]; however we found no similar study previously preformed in pediatric age groups elsewhere, and our study seems to be the first to have preformed such a comparison.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study done by Kato et al in Japanese children showed eradication rates of 87.5% for proton pump inhibitors (PPI), amoxicillin, and metronidazole, and 77.4% for PPI, amoxicillin, and clarithromycin [13]. However in 2004 Bahremand et al preformed a study in Tehran, Iran, that showed eradication rates of 92% for omeprazole, clarithromycin, and amoxicillin and 84% for omeprazole, amoxicillin, metronidazole, and bismuth subcitrate, thus suggesting PPI, amoxicillin, and clarithromycin triple therapy as first-line eradication treatment in Iranian children [14]. Many studies preformed in adult populations have showed regimes containing amoxicillin-clavulanic acid to be more effective than those with amoxicillin in treatment of H. pylori infection [9,10,15]; however we found no similar study previously preformed in pediatric age groups elsewhere, and our study seems to be the first to have preformed such a comparison.…”
Section: Discussionmentioning
confidence: 99%
“…At this moment, in Europe only omeprazole and esomeprazole are approved [18]. Almost all published efficacy studies in pediatric patients have been performed with omeprazole and lansoprazole [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37] used in combination therapies for the first-line treatment of H. pylori eradication. The North American Society for Pediatric Gastroenterology, Hepatology and Nutrition published clinical practice guidelines on the use of omeprazole for management of gastroesophageal reflux disease in infants and children [38].…”
Section: Ppi For H Pylori Eradicationmentioning
confidence: 99%
“…These guidelines have been extrapolated in pediatric efficacy studies for the management of H. pylori eradication in children. In fact, similar dose regimens have applied to omeprazole- (and lansoprazole-) based dual and triple eradication therapies for H. pylori in children [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. …”
Section: Ppi For H Pylori Eradicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested quadruple therapy as the first-line of therapy for the eradication of H. pylori infection in children in their geographic area. Treatment of H. pylori infection in children with protocols containing bismuth compounds have been reported with variable success [4][5][6][7]. In a recent report of pooled data [8], bismuth triple therapies were found to be more efficacious than proton pump inhibitor triple therapies (77 vs. 64%) as a first-line treatment.…”
mentioning
confidence: 99%